Self-heating material as well as preparation method and application thereof
By bonding conductive carbon paper or carbon fiber cloth to porous metal materials, an integrated self-heating material is formed and in contact with alkaline electrolytes, the problems of slow heating speed and severe reaction of traditional self-heating materials are solved, and a fast and controllable heating effect is achieved.
Patent Information
- Application Number
- CN202411807059.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-28
AI Technical Summary
Traditional self-heating materials have problems such as slow heating rate, excessive reaction, catalytic reactions required for exogenous conditions, or difficult temperature control.
Conductive carbon paper or carbon fiber cloth is used as the positive electrode material layer, and bonded with porous metal material as the negative electrode material layer to form an integrated self-heating material. When this material comes into contact with the alkaline electrolyte, the alkaline electrolyte passes through the porous structure of the negative electrode material layer and the negative electrode material, causing a short-circuit reaction of the metal air battery to achieve heating.
It has achieved the advantages of fast heating, controllable temperature, and long-lasting heating time, and is convenient to store and use, without the risk of burning and explosion.
Smart Images

Figure CN119529778A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of self-heating materials, and in particular to a self-heating material, a preparation method thereof and applications thereof. Background Art
[0002] Self-heating technology was originally developed to meet the needs of military field operations. It is mainly used for self-heating food for individual soldiers, of which self-heating materials are the core component. Self-heating materials refer to materials that can generate heat through chemical reactions or physical processes, among which chemical reaction self-heating materials are the most common. The principle is that when a chemical heating agent comes into contact with specific conditions, such as air, moisture or other chemicals, a chemical reaction will occur and release heat.
[0003] The earliest self-heating technology used the hydration reaction of quicklime to release heat, that is, heat is released during the reaction of CaO and H2O to generate Ca(OH)2. In order to meet the application needs of different scenarios, self-heating materials such as iron-carbon type, nano / micron metal oxidation type, aluminum water reaction type, magnesium water reaction type, metal and strong oxidant reaction type and aluminum thermite reaction type have gradually come out, but the above self-heating materials have problems such as slow heating speed, too violent reaction, need for external conditions to catalyze the reaction or difficult to control the temperature.
[0004] Therefore, traditional self-heating materials need further improvement. Summary of the invention
[0005] Based on this, one or more embodiments of the present application provide a self-heating material that is easy to use, generates heat quickly, and has controllable temperature, and a preparation method thereof, a self-heating component, a self-heating device, and applications thereof, and correspondingly provide a heated cigarette smoking body and a heated cigarette containing the above-mentioned self-heating material.
[0006] According to a first aspect of the present application, a self-heating material is provided, the self-heating material comprising a positive electrode material layer, a negative electrode material layer and a bonding layer, the bonding layer bonding the positive electrode material layer and the negative electrode material layer to form a whole, the positive electrode material layer and the negative electrode material layer are at least partially in contact;
[0007] The positive electrode material layer includes conductive carbon paper or carbon fiber cloth, and the negative electrode material layer includes porous metal material.
[0008] In some embodiments, the self-heating material satisfies at least one of the following characteristics:
[0009] (1) The porosity of the positive electrode material layer is 60% to 90%;
[0010] (2) The density of the positive electrode material layer is 0.01 g / cm 3 ~0.5 g / cm3 ;
[0011] (3) The plane resistivity of the positive electrode material is 4 mΩ·cm 2 ~10 mΩ·cm 2 ;
[0012] (4) The thickness of the positive electrode material layer is 0.1 mm to 0.4 mm.
[0013] In some of the embodiments, the porosity of the negative electrode material layer is 20% to 50%.
[0014] In some embodiments, the porous metal material includes one or more of a metal mesh, a porous metal plate, a porous metal foil, and a porous metal belt.
[0015] In some embodiments, the porous metal material is made of one or more of aluminum, magnesium, zinc and iron.
[0016] In some of the embodiments, the bonding layer includes a bonding agent, and the bonding agent includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, potassium polyacrylate, potassium polyacrylate and polyacrylamide.
[0017] According to the second aspect of the present application, a method for preparing the above-mentioned self-heating material is provided, comprising the following steps:
[0018] The positive electrode material layer and the negative electrode material layer are stacked, a binder is coated between the positive electrode material layer and the negative electrode material layer, and the layers are pressed and formed to obtain the self-heating material.
[0019] In some of the embodiments, the pressing pressure is 5 MPa~15 MPa.
[0020] According to a third aspect of the present application, a self-heating component is provided, comprising an alkaline electrolyte and the self-heating material described above, wherein the alkaline electrolyte and the self-heating material are placed separately.
[0021] In some embodiments, the alkaline electrolyte includes one or more of potassium hydroxide and its hydrates, sodium hydroxide and its hydrates, lithium hydroxide and its hydrates, calcium hydroxide and its hydrates, potassium carbonate and its hydrates, sodium carbonate and its hydrates, lithium carbonate and its hydrates, calcium carbonate and its hydrates, potassium bicarbonate and its hydrates, sodium bicarbonate and its hydrates, lithium bicarbonate and its hydrates, and calcium bicarbonate and its hydrates.
[0022] According to a fourth aspect of the present application, a self-heating device is provided, comprising the above-mentioned self-heating component.
[0023] According to a fifth aspect of the present application, an application method of the above-mentioned self-heating device is provided, wherein an alkaline electrolyte is brought into contact with a self-heating material.
[0024] According to the sixth aspect of the present application, a heated cigarette smoke body is provided, comprising an aerosol matrix, cigarette paper and the above-mentioned self-heating material; the cigarette paper is wrapped around the outside of the aerosol matrix, and the self-heating material is located between the aerosol matrix and the cigarette paper.
[0025] According to a seventh aspect of the present application, a heated cigarette is provided, comprising the heated cigarette smoke-generating body described above.
[0026] Compared with the traditional technology, this application has the following beneficial effects:
[0027] The self-heating material of the present application uses a sheet material such as conductive carbon paper or carbon fiber cloth as the positive electrode material, and bonds it with a negative electrode material having a porous structure. When the self-heating material thus obtained contacts with an alkaline electrolyte, the alkaline electrolyte can pass through the porous structure of the negative electrode material layer and contact the positive electrode material and the negative electrode material. After the three contact, a short-circuit reaction of the metal-air battery occurs, thereby generating heat. The self-heating material of the present application has the advantages of rapid heating, controllable temperature, and long-lasting heating time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 This is a schematic diagram of the structure of a heated cigarette smoke-generating body in one embodiment of the present application.
[0030] Explanation of reference numerals: 10, aerosol matrix; 20, cigarette paper; 30, self-heating material; 31, positive electrode material layer; 32, bonding layer; 33, negative electrode material layer. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0033] In a first aspect of the present application, a self-heating material is provided, the self-heating material comprising a positive electrode material layer, a negative electrode material layer and a bonding layer, wherein the bonding layer bonds the positive electrode material layer and the negative electrode material layer to form a whole, and the positive electrode material layer and the negative electrode material layer are at least partially in contact;
[0034] The positive electrode material layer includes conductive carbon paper, conductive carbon film or carbon fiber cloth, and the negative electrode material layer includes porous metal material.
[0035] The self-heating material of the present application uses sheet materials such as conductive carbon paper or carbon fiber cloth as the positive electrode material, and bonds it to a negative electrode material with a porous structure. When the self-heating material thus obtained comes into contact with an alkaline electrolyte, the alkaline electrolyte can pass through the porous structure of the negative electrode material layer and come into contact with the positive electrode material and the negative electrode material. After the three come into contact, a short-circuit reaction of the metal-air battery occurs, thereby achieving heat generation.
[0036] In some embodiments, the adhesive layer includes an adhesive, and the adhesive includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, potassium polyacrylate, potassium polyacrylate and polyacrylamide. The above adhesive can be cross-linked with the alkaline electrolyte to form a polymer electrolyte.
[0037] It is understood that the bonding layer is located between the positive electrode material layer and the negative electrode material layer, and the positive electrode material layer and the negative electrode material layer are bonded to each other through the adhesive bonding layer. The size of the bonding layer can be completely overlapped with the positive electrode material or the negative electrode material, or it can be partially overlapped.
[0038] In some embodiments, the positive electrode material layer and the negative electrode material layer are the same size.
[0039] In some embodiments, the positive electrode material layer is in contact with the entirety of the negative electrode material layer.
[0040] In some embodiments, the mass ratio of the positive electrode material layer to the negative electrode material layer is (0.4-0.6): 1. As an example, the mass ratio of the positive electrode material layer to the negative electrode material layer can be 0.4:1, 0.41:1, 0.42:1, 0.43:1, 0.44:1, 0.45:1, 0.46:1, 0.47:1, 0.48:1, 0.49:1, 0.5:1, 0.51:1, 0.52:1, 0.53:1, 0.54:1, 0.55:1, 0.56:1, 0.57:1, 0.58:1, 0.59:1, 0.6:1, or any value within the range formed by any two of the above point values.
[0041] In some embodiments, the porosity of the positive electrode material layer is 60% to 90%. As an example, the porosity of the positive electrode material layer can be 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, or any value within the range formed by any two of the above point values.
[0042] It can be understood that when the porosity of the positive electrode material layer is within the above range, the alkaline electrolyte can penetrate the positive electrode material layer more quickly.
[0043] In some embodiments, the density of the positive electrode material layer is 0.01 g / cm 3 ~0.5 g / cm 3. As an example, the density of the positive electrode material layer can be 0.01 g / cm³, 0.02 g / cm³, 0.03 g / cm³, 0.04 g / cm³, 0.05 g / cm³, 0.06 g / cm³, 0.07 g / cm³, 0.08 g / cm³, 0.09 g / cm³, 0.1 g / cm³, 0.11 g / cm³, 0.12 g / cm³, 0.13 g / cm³, 0.14 g / cm³, 0.15 g / cm³, 0.16 g / cm³, 0.17 g / cm³, 0.18 g / cm³, 0.19 g / cm³, 0.2 g / cm³, 0.21 g / cm³, 0.22 g / cm³, 0.23 g / cm³, 0.24 g / cm³, 0.25 g / cm³, 0.26 g / cm³, 0.27 g / cm³、0.28 g / cm³、0.29 g / cm³、0.3 g / cm³、0.31 g / cm³、0.32 g / cm³、0.33 g / cm³、0.34 g / cm³、0.35 g / cm³、0.36 g / cm³、0.37 g / cm³、0.38 g / cm³, 0.39 g / cm³, 0.4 g / cm 3 , 0.41 g / cm 3 , 0.42 g / cm 3 , 0.43 g / cm 3 , 0.44 g / cm 3 , 0.45 g / cm 3 , 0.46 g / cm 3 , 0.47 g / cm 3 , 0.48 g / cm 3 , 0.49 g / cm 3 , 0.5 g / cm 3 , or any value within the range formed by any two of the above point values.
[0044] In some embodiments, the planar resistivity of the positive electrode material is 4 mΩ·cm 2 ~10 mΩ·cm 2 As an example, the planar resistivity of the cathode material may be 4 mΩ·cm 2 , 5 mΩ·cm 2 、6 mΩ·cm 2 、7 mΩ·cm 2 、8 mΩ·cm 2 , 9 mΩ·cm 2 , 10 mΩ·cm 2 , or any value within the range formed by any two of the above point values.
[0045] It can be understood that when the plane resistivity of the positive electrode material layer is within the above range, it can effectively conduct the OH- ions generated after the positive electrode oxygen participates in the reaction, improve the battery resistance, enhance the battery performance, and improve the heat generation efficiency during short circuit.
[0046] In some embodiments, the thickness of the positive electrode material layer is 0.1 mm to 0.4 mm. As an example, the thickness of the positive electrode material layer can be 0.1 mm, 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm, 0.2 mm, 0.21 mm, 0.22 mm, 0.23 mm, 0.24 mm, 0.25 mm, 0.26 mm, 0.27 mm, 0.28 mm, 0.29 mm, 0.3 mm, 0.31 mm, 0.32 mm, 0.33 mm, 0.34 mm, 0.35 mm, 0.36 mm, 0.37 mm, 0.38 mm, 0.39 mm, 0.4 mm, or any value within the range formed by any two of the above point values.
[0047] In some embodiments, the positive electrode material layer is a hydrophilic material. It is understood that when the hydrophilic material is in contact with the alkaline electrolyte, the alkaline electrolyte can penetrate through the hydrophilic material to contact the negative electrode material layer.
[0048] In some embodiments, the positive electrode material layer is selected from conductive carbon paper, and the conductive carbon paper is selected from conductive carbon paper with product model TGP-H-060 produced by Toray of Japan or conductive carbon paper with product model W01S1011 produced by Carbon Energy of Taiwan, China.
[0049] In some embodiments, the thickness of the negative electrode material layer is 0.04 mm to 0.05 mm. As an example, the thickness of the negative electrode material layer can be 0.04 mm, 0.05 mm, 0.06 mm, or any value within the range formed by any two of the above point values.
[0050] Optionally, the thickness of the negative electrode material layer is 0.05 mm.
[0051] In some embodiments, the porosity of the negative electrode material layer is 20% to 50%. The porosity of the negative electrode material layer can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, or any value within the range formed by any two of the above point values.
[0052] In some embodiments, the porous metal material includes one or more of a metal mesh, a porous metal plate, a porous metal foil, and a porous metal belt.
[0053] In the present application, a metal material with a continuous shape such as a metal mesh, a porous metal plate, a porous metal foil or a porous metal belt is used as the negative electrode material layer, which can reduce the generation of debris and dust during the storage process and the reaction process, thereby reducing pollution to the environment and harm to human health.
[0054] In some embodiments, the porous metal material is made of one or more of aluminum, magnesium, zinc and iron.
[0055] Optionally, the raw material of the negative electrode material layer is selected from aluminum, for example, it can be one or more of aluminum wire mesh, porous aluminum plate, porous aluminum foil and porous aluminum tape.
[0056] When aluminum is used as the negative electrode material and in contact with an alkaline electrolyte, the reaction between the negative electrode material layer and the alkaline electrolyte is Al+4OH - →Al(OH)4 - +3e - ; The reaction between the positive electrode material layer and the alkaline electrolyte is O2+2H2O+4e - →4OH - The total reaction is 4Al+3O2+6H2O→4Al(OH)3 (△H=-31.72kJ / g). This reaction can occur at room temperature. The oxygen in the air is adsorbed by activated carbon to form the "positive electrode site" of the primary battery. After adding inorganic electrolyte, it will form several micro short-circuit points between the "negative electrode site" of the negative electrode metal, and the reaction rate will increase.
[0057] The above-mentioned self-heating material of the present application can reach a high temperature of more than 50°C within 11 seconds, and can maintain above 50°C for more than 45 seconds; the maximum temperature can be controlled between 65°C and 100°C.
[0058] The above-mentioned self-heating material of the present application does not need to be isolated from air during storage, and does not need to add exogenous water or exogenous heat to start the reaction. It has the advantages of convenient storage and easy use; and has the advantages of being light and thin, heating up quickly, temperature controllable, no risk of combustion and explosion, and high heating efficiency.
[0059] In a second aspect of the present application, a method for preparing the above-mentioned self-heating material is provided, comprising the following steps:
[0060] The positive electrode material layer and the negative electrode material layer are stacked, a binder is coated between the positive electrode material layer and the negative electrode material layer, and the layers are pressed and formed to obtain a self-heating material.
[0061] It can be understood that a binder is coated between the positive electrode material layer and the negative electrode material layer, and a binder layer with uniform thickness can be formed after pressing, so that the positive electrode material layer and the negative electrode material layer can be tightly bonded.
[0062] In some embodiments, the pressure of the press molding is 5 MPa to 15 MPa. As an example, the pressure of the press molding can be 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa, 15 MPa, or any value within the range formed by any two of the above point values. Optionally, the pressure of the press molding is 8 MPa.
[0063] The self-heating material of the present application has the advantages of simple process and easy operation.
[0064] In a third aspect of the present application, a self-heating component is provided, comprising an alkaline electrolyte and the self-heating material described above, wherein the alkaline electrolyte and the self-heating material are placed separately.
[0065] In some embodiments, the alkaline electrolyte includes one or more of potassium hydroxide and its hydrates, sodium hydroxide and its hydrates, lithium hydroxide and its hydrates, calcium hydroxide and its hydrates, potassium carbonate and its hydrates, sodium carbonate and its hydrates, lithium carbonate and its hydrates, calcium carbonate and its hydrates, potassium bicarbonate and its hydrates, sodium bicarbonate and its hydrates, lithium bicarbonate and its hydrates, and calcium bicarbonate and its hydrates.
[0066] In some optional embodiments, the alkaline electrolyte is a liquid electrolyte. It is understandable that the liquid electrolyte can more easily pass through the pores on the surface of the positive electrode material layer and the negative electrode material layer in the self-heating material, thereby further improving the heat generation efficiency.
[0067] In a fourth aspect of the present application, a self-heating device is provided, comprising the self-heating component described above.
[0068] In a fifth aspect, the present application provides an application method of the self-heating device, which brings an alkaline electrolyte into contact with a self-heating material.
[0069] In the sixth aspect of the present application, a heated cigarette smoke body is provided, comprising an aerosol matrix 10, a cigarette paper 20 and the above-mentioned self-heating material 30; the cigarette paper 20 is wrapped around the outside of the aerosol matrix 10, and the self-heating material 30 is located between the aerosol matrix 10 and the cigarette paper 20.
[0070] In some embodiments, the self-heating material 30 includes a positive electrode material layer 31 , a negative electrode material layer 33 , and a bonding layer 32 , wherein the bonding layer 32 is located between the positive electrode material layer 31 and the negative electrode material layer 33 .
[0071] In some embodiments, the structure of the heated cigarette smoking body is as follows Figure 1 shown.
[0072] The present application does not specifically limit the positional relationship between the positive electrode material layer 31 and the negative electrode material layer 33 in the heated cigarette smoke body, that is, the positive electrode material layer can be located on the side in contact with the aerosol matrix or on the side in contact with the cigarette paper.
[0073] The heated cigarette smoking body of the present application comprises the above-mentioned self-heating material, and when in use, it is in contact with an alkaline electrolyte, which can not only quickly release a certain amount of heat, but also reduce the amount of heat required to be provided by an external heating device.
[0074] Understandably, the alkaline electrolyte is dripped between the positive electrode material layer and the negative electrode material layer in the heated cigarette smoke body through a syringe, so as to contact the positive electrode material layer and the negative electrode material layer.
[0075] In a seventh aspect, the present application provides a heated cigarette, comprising the heated cigarette smoke-generating body described above.
[0076] In some of the embodiments, the heated cigarette further includes a filter segment and a hollow segment; the filter, the hollow segment and the aerosol matrix are arranged in sequence.
[0077] When heated cigarettes are used, an external heating device is required to heat the aerosol matrix to produce aerosol. When heated cigarettes contain the above-mentioned self-heating materials, heat is generated by contact with alkaline electrolytes during use, which can replace the heat generated by the heating device to a certain extent, thereby reducing the energy consumption of the heating device.
[0078] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0079] Example 1
[0080] The conductive carbon paper with the product model TGP-H-060 produced by Toray Industries, Japan, was used as the positive electrode material layer; the conductive carbon paper had a porosity of 78%, a thickness of 0.19 mm, and a plane resistivity of 5.8 mΩ·cm 2 , density is 0.44 g / cm 3 , size is 4cm×4cm.
[0081] A porous aluminum foil with a thickness of 0.05 mm, a porosity of 20%, and a size of 4 cm × 4 cm was used as the negative electrode material layer.
[0082] The positive electrode material layer and the negative electrode material layer are stacked, and about 0.2 g of potassium polyacrylate solution is coated between the two as a binder. The layers are cold-pressed on a roller machine at a pressure of 8 MPa to obtain a self-heating material including an adhesive layer.
[0083] At room temperature of 26°C, the self-heating material prepared in Example 1 was placed in a glass chromatographic bottle with a mouth diameter of 8 mm, a volume of 4 mL, and a bottle cap. A hole was punched in the bottle cap to insert an ultrafine thermocouple. 0.5 mL of KOH with a concentration of 6 mol / L was dripped onto the self-heating material using a syringe, the bottle cap was tightened, and the thermocouple wire was inserted. The thermocouple was connected to a temperature sensor to record temperature changes in real time.
[0084] The results show that the self-heating material prepared in this embodiment can heat up to 50°C in 10 s, the maximum temperature can reach 75.5°C, and can last above 50°C for 63 s.
[0085] Example 2
[0086] It is basically the same as Example 1, except that:
[0087] The conductive carbon paper with the product model of China Taiwan Carbon Energy W01S1011 produced by China Taiwan Carbon Energy Technology Co., Ltd. was used as the positive electrode material layer; the conductive carbon paper had a porosity of 68%, a thickness of 0.36 mm, and a resistivity of 4.8 mΩ·cm 2 , density is 0.013 g / cm 2 , size is 4 cm×4 cm.
[0088] An aluminum mesh with a thickness of 0.05 mm, a porosity of 20%, and a size of 4 cm × 4 cm was used as the negative electrode material layer.
[0089] Example 3
[0090] It is basically the same as Example 1, except that:
[0091] An equal mass of polyvinyl alcohol solution is used to replace potassium polyacrylate solution as a binder.
[0092] Example 4
[0093] It is basically the same as Example 2, except that:
[0094] An equal mass of polyvinyl alcohol solution is used to replace potassium polyacrylate solution as the binder.
[0095] Example 5
[0096] It is basically the same as Example 1, except that:
[0097] An aluminum-magnesium alloy porous metal foil of equal mass is used to replace the porous aluminum foil; the mass ratio of aluminum to magnesium in the aluminum-magnesium alloy is 9:1.
[0098] Example 6
[0099] It is basically the same as Example 2, except that:
[0100] An aluminum-magnesium alloy porous metal foil of equal mass is used to replace the porous aluminum foil; the mass ratio of aluminum to magnesium in the aluminum-magnesium alloy is 9:1.
[0101] Example 7
[0102] It is basically the same as Example 1, except that:
[0103] An aluminum-zinc alloy porous metal foil of equal mass is used to replace the porous aluminum foil; the mass ratio of aluminum to zinc in the aluminum-zinc alloy is 9:1.
[0104] Example 8
[0105] It is basically the same as Example 2, except that:
[0106] An aluminum-zinc alloy porous metal foil of equal mass is used to replace the porous aluminum foil; the mass ratio of aluminum to zinc in the aluminum-zinc alloy is 9:1.
[0107] Example 9
[0108] The method is basically the same as Example 1, except that the conductive carbon paper with the product model number W01S1011 from Taiwan Carbon Energy Co., Ltd. is used instead of the conductive carbon paper with the product model number TGP-H-060.
[0109] Example 10
[0110] It is basically the same as Example 1, except that a homemade air positive electrode carbon film is used instead of the conductive carbon paper with the product model number TGP-H-060.
[0111] Preparation method of air positive electrode carbon film: 1. Preparation of air positive electrode material: The electrode material is mixed in a ratio of 50wt% activated carbon, 30wt% acetylene black, and 20wt% polymer binder polytetrafluoroethylene PTFE. The above materials are all solid powders, grind together for 10 minutes to make them evenly mixed, add organic solvent N-methylpyrrolidone to a solid matter content of 25g / mL, and ultrasonically vibrate for 30 minutes to form a uniform and stable paste suspension. The suspension containing the electrode material is evenly coated on a 4 cm×4 cm glass plate and dried at room temperature for 24 hours to obtain a flat air positive electrode material.
[0112] Comparative Example 1
[0113] Mix 0.6 g of aluminum powder with a particle size of 400 mesh and 0.3 g of activated carbon powder with a particle size of 325 mesh, place the mixture in a glass chromatographic bottle, add 1 mL of KOH with a concentration of 6 mol / L into the glass chromatographic bottle with a syringe, screw on the bottle cap and insert the thermocouple wire; connect the thermocouple to the temperature sensor to record the temperature changes in real time.
[0114] The mixture of Comparative Example 1 reacted violently after contacting with KOH, and a sharp temperature rise was detected in the glass bottle, with the highest temperature reaching 259.1° C. within 5 s.
[0115] Comparative Example 2
[0116] A porous aluminum foil with a thickness of 0.05 mm and a porosity of 20% was placed in a glass chromatographic bottle. 1 mL of 6 mol / L KOH was added to the glass chromatographic bottle using a syringe. The bottle cap was screwed on and a thermocouple wire was inserted. The thermocouple was connected to a temperature sensor to record temperature changes in real time.
[0117] When the porous aluminum foil of Comparative Example 2 reacted with KOH, bubbles were generated without a sharp temperature rise, and the highest temperature was only 34.5°C.
[0118] The raw material parameters of the self-heating film materials in the above-mentioned Examples 1-10 and Comparative Examples 1-2 are shown in Table 1, and the heating performance results of the self-heating film materials are shown in Table 2.
[0119] Table 1
[0120]
[0121] Table 2
[0122]
[0123] After the self-heating material prepared in the above embodiment of the present application comes into contact with an alkaline electrolyte, it can reach a high temperature of more than 50°C within 16 seconds and can be maintained at more than 50°C for more than 35 seconds; the maximum temperature can be controlled between 60°C and 100°C.
[0124] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0125] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A self-heating material, characterized in that: The self-heating material comprises a positive electrode material layer, a negative electrode material layer and a bonding layer, wherein the bonding layer bonds the positive electrode material layer and the negative electrode material layer to form a whole, and the positive electrode material layer and the negative electrode material layer are at least partially in contact; The positive electrode material layer includes conductive carbon paper or carbon fiber cloth, and the negative electrode material layer includes porous metal material.
2. The self-heating material according to claim 1, characterized in that: The self-heating material satisfies at least one of the following characteristics: (1) The porosity of the positive electrode material layer is 60% to 90%; (2) The density of the positive electrode material layer is 0.01 g / cm 3 ~0.5 g / cm 3 ; (3) The plane resistivity of the positive electrode material is 4 mΩ·cm 2 ~10 mΩ·cm 2 ; (4) The thickness of the positive electrode material layer is 0.1 mm to 0.4 mm.
3. The self-heating material according to any one of claims 1 to 2, characterized in that: The porosity of the negative electrode material layer is 20% to 50%.
4. The self-heating material according to any one of claims 1 to 2, characterized in that: The porous metal material includes one or more of a metal mesh, a porous metal plate, a porous metal foil and a porous metal belt.
5. The self-heating material according to claim 4, characterized in that: The porous metal material includes one or more of aluminum, magnesium, zinc and iron.
6. The self-heating material according to any one of claims 1 to 2 and 5, characterized in that: The bonding layer includes a bonding agent, and the bonding agent includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, potassium polyacrylate, potassium polyacrylate and polyacrylamide.
7. A method for preparing the self-heating material according to any one of claims 1 to 6, characterized in that: The steps include: The positive electrode material layer and the negative electrode material layer are stacked, a binder is coated between the positive electrode material layer and the negative electrode material layer, and the layers are pressed and formed to obtain the self-heating material.
8. The method for preparing the self-heating material according to claim 7, characterized in that: The pressing pressure is 5 MPa to 15 MPa.
9. A self-heating component, characterized in that: It comprises an alkaline electrolyte and the self-heating material according to any one of claims 1 to 6, wherein the alkaline electrolyte is placed separately from the self-heating material.
10. The self-heating component according to claim 9, characterized in that: The alkaline electrolyte includes one or more of potassium hydroxide and its hydrate, sodium hydroxide and its hydrate, lithium hydroxide and its hydrate, calcium hydroxide and its hydrate, potassium carbonate and its hydrate, sodium carbonate and its hydrate, lithium carbonate and its hydrate, calcium carbonate and its hydrate, potassium bicarbonate and its hydrate, sodium bicarbonate and its hydrate, lithium bicarbonate and its hydrate, and calcium bicarbonate and its hydrate.
11. A self-heating device, characterized in that: The invention comprises the self-heating component as described in any one of claims 9 to 10.
12. The application method of the self-heating device according to claim 11, characterized in that: An alkaline electrolyte is brought into contact with the self-heating material.
13. A heated cigarette smoke-generating body, characterized in that: It comprises an aerosol matrix, cigarette paper and the self-heating material according to any one of claims 1 to 6; the cigarette paper is wrapped around the outside of the aerosol matrix, and the self-heating material is located between the aerosol matrix and the cigarette paper.
14. A heated cigarette, characterized in that: Including the heated cigarette smoke-generating body as described in claim 13.